Analisis Pengelolaan Zakat, Infaq dan Sedekah Untuk Meningkatkan Ekonomi Dhuafa Pada Masjid Al Muhajirin Perumahan BSP Mojokerto - Maulana, Muhammad Iqbal; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2020)
This study aims 1) To find out the strategies of zakat, infaq and alms management to improve the economy of the poor at the Amil Zakat Institution in Mojokerto City and 2) To find out the obstacles and opportunities in managing zakat, infaq, and alms to improve the poor economy at the Amil Zakat Institution in Mojokerto City. The data analysis method in this study was conducted using the Miles and Huberman models. The results showed that the management of zakat, infaq, and alms to improve the economy of the underprivileged. The main purpose of zakat, infaq, and alms is community welfare, this fact makes zakat can function as a source of socioeconomic funds for Muslims. Internal barriers that are usually about the needs of the preparation of needs with different budgets so that it is often an inaccuracy in the management process carried out. The main obstacle that causes zakat has not been able to influence the economy and the opportunities in the management process can make the activities carried out more productive and in accordance with the provisions set.